Genetic relationships among 81 dendrobium accessions from Malaysia - Nor Hazlina, M.S.; Wahba, L.E.; Fadelah, A.; Wickneswari, R. (Penerbit Universiti Kebangsaan Malaysia, 2013)
In breeding programs, the information on the relationships among the species and hybrids is important to make the correct choice of parents for hybrid production. In this study we addressed the relationship among 81 Dendrobium accessions (13 Dendrobium species, 8 commercial hybrids and 17 interspecific hybrid progenies) with 16 morphological traits. Data was analyzed using unweighted pair group method with arithmetic averages (UPGMA) cluster analysis. The results of characterization analysis revealed a high diversity between the Dendrobium accessions. Dendrobium accessions were grouped into three well-defined clusters. The first cluster consisted of 4 species, 8 commercial hybrids and 17 interspecific hybrid progenies. The second cluster consisted of 8 Dendrobium species. The third cluster comprised 1 Dendrobium species. These results indicated that the morphological characters were adequate in distinguishing between the species, commercial hybrids and interspecific hybrid progenies according to the species section and geographic origin.